Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $p$ be an odd prime and $\omega$ be a primitive $p$th root of unity. The question is to prove that:

$$(1-\omega)(1-\omega^2) \cdots (1-\omega^{p-1})=p$$


What I have done so far is:

I can see that this is true for $p=3$

$$(1-\omega)(1-\omega^2)=1-(\omega+\omega^2)+w^3=1-(-1)+1=3=p$$

I am not able to prove this in general....

$$(1-\omega)(1-\omega^2) \cdots (1-\omega^{p-1})=1-(\omega+\omega^2+\cdots+\omega^{p-1})+????+\omega^{\frac{p(p-1)}{2}}$$

I do not have any idea what that $????$ could be but all I can say is:

  • $(\omega+\omega^2+\cdots +\omega^{p-1})=-1$
  • $\omega^{\frac{p(p-1)}{2}}=1$

So, $(1-\omega)(1-\omega^2)\cdots (1-\omega^{p-1})=3+????$

I am not able to do more than this.

There could be some (hard) way of doing it by hand multiplying all those things but I am looking for a more theoretical idea.

Please help me to clear this up.

share|improve this question

3 Answers 3

up vote 5 down vote accepted

Recall the formula for the summation $1+x+x^2+\cdots+x^n = {x^{n+1}-1 \over x-1}$ when $x\neq 1$.

In particular, this shows that $f(x)=x^{p}-1 =(1+x+x^2+\cdots+x^{p-1})(x-1)$.

Since $\omega$ is a root of unity, we have $f(\omega^k) = 0$ for $k=0,...,p-1$.

Since $\omega$ is primitive, $\omega^0,...,\omega^{p-1}$ are distinct and so $f(x) = (x-1)\cdots (x-\omega^{p-1}) $.

Hence $1+x+x^2+\cdots+x^{p-1} = (x-\omega^1)\cdots (x-\omega^{p-1}) $.

share|improve this answer
    
all i can say is i was stupid.... I was neglecting $(x-1)$ in factorization of $x^p-1$ and that created all that mess... this is natural.... Thank you... –  Praphulla Koushik May 23 at 15:36
    
Glad to help! ${}{}$ –  copper.hat May 23 at 15:39

Hint: what does $x^n-1$ look like factored?

share|improve this answer
2  
Nice hint that just gives away the right amount of information. Also your hidden argument shows that $p$ could be any integer be it prime or not. –  Peder May 23 at 13:56
    
Yes Yes... I got it.. Thank you :) –  Praphulla Koushik May 23 at 15:42
    
@Peder : I for got to mention this but this does not hold for any integer but only primes.... –  Praphulla Koushik May 24 at 2:28
    
@sea : I guess you also mean $n$ to be prime... Factorization and all other holds smoothly but result is totally dependent on $n$ being prime... –  Praphulla Koushik May 24 at 2:31
    
@Praphulla: Try $n=4$, $\omega=i$: $(1-i)(1-(-1))(1+i)=4$, so it holds for non-primes as well. –  Peder May 24 at 2:42

Let $f(x)=x^p-1$ and $g(x)=f(1-x)$. Then $g(1-\omega^k)=f(\omega^k)=0$ for all $k$.

$(1-\omega)(1-\omega^2)\cdots (1-\omega^{p-1})$ is thus the product of all roots of $g$ except $0$. So, expand $g$, factor $x$, and look at the independent term.

share|improve this answer
    
This is another nice way... Thank you :) –  Praphulla Koushik May 23 at 15:39

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.